Highly improved mechanical and dielectric properties of paper-based composites with polyimide chopped fiber functionalized by ethylenediamine. (September 2019) - Xie, Fan; Zhang, Nan; Lu, Zhaoqing; Zhuo, Longhai; Yang, Bin; Song, Shunxi; Qin, Panliang; Wei, Ning
In this study, polyimide (PI) chopped fibers were modified by ethylenediamine, and PI paper-based composites were fabricated using the as-modified PI chopped fibers and para-aramid fibrids which served as raw materials through the wet-forming process. The influence of different alkali treatment durations on the properties of PI fibers and composites was investigated. In sharp contrast with the pristine PI fibers, there was a satisfying difference in modified PI fibers including rougher surfaces and improved wettability due to the introduction of hydrophilic groups as confirmed by scanning electron microscope and Fourier transform infrared spectrometer. With increase in the modification time, the tensile index, the tearing index, and the internal bond strength of the composites were improved by 40.6, 27.0, and 103.57%, respectively, due to the hydrogen bonds. Meanwhile, the dielectric strength of the composites increased by 77.2% compared with the unmodified ones. These remarkable changes were mainly attributed to the enhanced interfacial bonding of the composites and decreased porosity in the three-dimensional network structure of the paper. Moreover, thermal stability was kept preferably within a certain range in spite of slight decrease.